2014
DOI: 10.1186/1471-2318-14-15
|View full text |Cite
|
Sign up to set email alerts
|

Multiple component interventions for preventing falls and fall-related injuries among older people: systematic review and meta-analysis

Abstract: BackgroundLimited attention has been paid in the literature to multiple component fall prevention interventions that comprise two or more fixed combinations of fall prevention interventions that are not individually tailored following a risk assessment. The study objective was to determine the effect of multiple component interventions on fall rates, number of fallers and fall-related injuries among older people and to establish effect sizes of particular intervention combinations.MethodsMedline, EMBASE, CINAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 37 publications
1
77
0
10
Order By: Relevance
“…79 Exercise does not appear to have an effect on depressive symptoms. 80 From 16 reviews including 11-159 trials and one overview regarding falls prevention, [73][74][75][76]78,[80][81][82][83][84][85][86][87][88][89][90] we found that exercise programmes assessing risk for falls and managing this, anti-slip devices in shoes, home safety assessment and modification and training in walking aid use, may help prevent falls. The strongest evidence related to exercise, which reduces the risk and rate of falls in community-dwelling older adults, 73,75,78,[81][82][83][84][85] though some authors advocate caution with using exercise interventions in frailer older adults.…”
Section: Physical Activity and Fallsmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Exercise does not appear to have an effect on depressive symptoms. 80 From 16 reviews including 11-159 trials and one overview regarding falls prevention, [73][74][75][76]78,[80][81][82][83][84][85][86][87][88][89][90] we found that exercise programmes assessing risk for falls and managing this, anti-slip devices in shoes, home safety assessment and modification and training in walking aid use, may help prevent falls. The strongest evidence related to exercise, which reduces the risk and rate of falls in community-dwelling older adults, 73,75,78,[81][82][83][84][85] though some authors advocate caution with using exercise interventions in frailer older adults.…”
Section: Physical Activity and Fallsmentioning
confidence: 99%
“…78,81 Falls risk assessment and management appears to be effective. 81,83 Falls prevention programmes may reduce falls risk by up to 10% and may also reduce the fear of falling and falls-related injuries; 75,76,80,85,[88][89][90] however, results are inconclusive in cognitively impaired older adults. 74 Walking aids should be correctly sized and adapted, recommended by a health professional and only used when necessary with training.…”
Section: Physical Activity and Fallsmentioning
confidence: 99%
“…A systematic review examined the effects of multiple interventions to prevent falls in older adults (60) and found that multicomponent interventions that were not tailored to individual risk factors were effective at reducing both the number of people who fell (pooled rate ratio = 0.85, 95% CI 0.80-0.91) as well as their rate of falls (pooled rate ratio = 0.80, 95% CI 0.72-0.89). This review presented the results of 17 trials with 5,034 participants.…”
Section: Multicomponent Interventions (Strong Evidence)mentioning
confidence: 99%
“…2,3 Studies show that some practices have the potential to reduce the prevalence of falls in older adults, such as performing physical exercise, the use of vitamin D supplements and organization of the home. 4,5 Other studies highlight changes in behavior and ways of life of older adults, for example, avoiding going up and down stairs, walking slowly, using orthotic support when necessary, correctly using medications, not drinking alcohol, crossing the street at pedestrian crossing points and wearing corrective lenses. 2,6 Studies in developed countries have advanced in the production of knowledge on fall prevention practices among older adults and have investigated the adherence and engagement of these people in fall prevention programs.…”
Section: Introductionmentioning
confidence: 99%